La campaña de África de la Unión Liberal. ¿una Crimea española? - Juan A. Inarejos Muñoz (L'Atelier du CRH)
The Union´s Liberal military expedition in Morocco. ¿An Spanish Crimean War ?From a general perspective the Spanish international interventions in the wars against Peru and Chile during the “bajoisabelino” period have been described as a part of a romantic and undefined foreign policy. Nevertheless this paper tries to refute this interpretative paradigm and to analyse the main reasons of the conflict and its impact in the articulation of nationalist rhetoric. Along this line, it also studies the leading role of the domestic policy and the public opinion to guide the foreign policy. Finally, this approach shed light into the research on international relations in two important topics, the relations between Spain and the most European powerful countries (the Victorian England and Napoleon III regime) and its strategies in the Northern Africa.